UJI KEAMANAN PADA WEBSITE JKL MENGGUNAKAN METODE PENETRATION TESTING EXECUTION STANDARD - Gito Putro Wardana, (2023)
A website is a collection of interconnected web pages that are generally located on the same server containing a collection of information provided by individuals, groups, or organizations. In today's world, the development of information technology is growing rapidly which has resulted in many people accessing the internet, especially visiting a website, from small children to adults. Websites that have a weak security system will be vulnerable to threat attacks that can occur at any time. Based on data obtained from the National Cyber and Crypto Agency (BSSN), there were 148 cases of website hacking in August 2022. In writing this thesis, a security test will be conducted on the JKL website. This is done to analyze the security of the website and how to overcome if any gaps are found. The method that will be used in writing this thesis is the Penetration Testing Execution Standard (PTES)